Equality and decent work achieving a gay work life in a straight workplace - Parreno, Emmanuel B. 1974-; Asuncion, Ronahlee A.; Teodosio, Virginia A.; Sison, Geodicio T.; Gaddi, Rebecca S. (2012)
This study explored the concept of equality at work and the framework of decent work in relation to the Lesbian, Gay, Bisexual and Transgender(LBGT)sector, specifically LGBTs in the formal sector. The study determined the presence of equality at work experienced by the LGBT sector, as operationalized by the Human Rights Campaign Corporate Equality Index. Also, the study evaluated whether or not structural , demographic and/or socio-cultural variables influence the degree of decent work experienced by the LGBT sector. Likewise, some of the socio-cultural variables were measured using the Attitudes Toward Lesbians and Gay Men Scale developed by Herek (1998). Moreover, a proposed Model of Decent Work for Filipino LGBTs was derived from the focus group discussions that were conducted.
"April 2012."
Vita.
Thesis (M. Industrial Relations)--University of the Philippines Diliman.
Keywords: Diversity in the workplace; Personnel management